THE EVOLUTION OF THE ROLE OF THE ACCOUNTING PROFESSION IN THE DIGITAL AGE: CHALLENGES AND OPPORTUNITIES - Mohammed Yahya Alhajjar (Scholar Express Journals, 2023)
to explore the evolution of the role of the accounting profession in the digital age. It also aims to analyze the challenges it faces, including legal, regulatory, professional and ethical challenges which are associated with this transformation. It also aims to explore the opportunities for professional advancement and improving accounting performance in terms of increasing efficiency and accuracy, improving decision-making processes and developing accountants' skills.
Keywords: Accounting Profession; Digital Age; Big Data